Dampak Keteladanan Hidup Keluarga Gembala Terhadap Keharmonisan Jemaat di GBI Serambi Salomo Makassar - Agus Prihanto; Andy Mulyadi Sapan; Saturi Saturi (Sekolah Tinggi Teologi Blessing Indonesia Makassar, 2023)
Abstract: Pastors and their families are important figures in church life. The exemplary life of the pastor's family is an attitude that the congregation often pays attention to. Pastoral families that do not set an example can have a negative impact on the life of the congregation. This can affect the life of the congregation including the harmony of the church family. The focus of the problem in this writing is how the pastoral family can be a good role model so that it can have an impact on the harmony of the congregational family. The research method used is the descriptive qualitative research method, with primary data sources from interviews and secondary data sources from journal articles on the internet. The harmony of the shepherd's family is a form of example for the congregation and this is a form of their ministry. The scope of exemplary family pastors includes integrity, being actively involved in service, paying attention to the congregation, not discriminating in service, being ready to serve, communicating, and being spiritual parents. Family harmony has the following characteristics: solving problems well, complementing each other, loving each other, openness, helping each other, togetherness, and honesty.Keywords: exemplary; shepherd family; The harmony of the church family Abstrak: Gembala dan keluarganya merupakan figur yang penting dalam kehidupan bergereja. Keteladanan hidup keluarga gembala merupakan sikap yang sering diperhatikan oleh jemaat. Keluarga gembala yang tidak memberi teladan dapat memberikan dampak yang buruk bagi kehidupan jemaat. Hal ini dapat mempengaruhi kehidupan jemaat termasuk keharmonisan keluarga jemaat. Fokus permasalahan dalam penulisann ini adalah bagaimana keluarga gembala dapat menjadi teladan yang baik, sehingga dapat memberi dampak pada keharmonisan keluarga jemaat. Metode penelitian yang digunakan yaitu metode penelitian kualitatif diskriptif, dengan sumber data primer dari hasil wawan cara dan sumber data skunder dari artikel-artikel jurnal dari internet. Keharmonisan keluarga gembala menjadi bentuk keteladanan bagi jemaat dan hal ini merupakan bentuk pelayanan mereka. Ruang lingkup keteladanan keluarga gembala antara lain berintegritas, terlibat aktif dalampelayanan, memberikan perhatian kepada jemaat, tidak membeda-bedakan dalampelayanan, siap sedia untuk melayani, komunikasi, dan menjadi orang tua rohani. Keharmonisan keluarga memiliki ciri-ciri :Menyelesaikan persoalan dengan baik, saling memperlengkapi, saling mengasihi, keterbukaan, tolong menolong, kebersamaan, dan kejujuran.Kata kunci : Keteladanan; Keluarga gembala; Keharmonisan keluarga jemaat